The relationship between learning style and writing performance of young learners in PowerPoint assisted classes - Radzi, Radzita; Mat Daud, Nuraihan (IIUM Press, 2012)
This paper discusses the correlation between young learners’ writing performance and their learning styles when PowerPoint was used in teaching writing skills. This study focuses on the sensory learning styles which comprises visual, auditory, kinesthetic and tactile learning styles (perceptual learning style). Reid’s (1995) ‘Perceptual Learning Style Preferences’ questionnaire was used to ascertain the students’ learning styles and a correlation analysis between their learning styles and writing performance was run. The analysis shows that there is no statitistically significant difference between the writing performance of the young learners in computer-assisted class and the traditional class. Their learning styles did not have a significant influence on their performance.